A new set of tools for Ethnobiologist in the COVID-19 Pandemic - Ladio, Ana H. (Ethnobiology and Conservation, 2020)
This article will develop a series of ideas for ethnobiologists to consider in their professional field from now on. One of the things we have most learned about indigenous communities is the importance of being committed to maintaining the networks of life and the protection of diversity. Considering the warnings given by indigenous groups regarding past and future imbalances of Nature, what will happen to ethnobiological work in the future, and is what we do really necessary? What lines of action, conflict, alliances and controversies lie ahead of us. The so-called new normality urges us to make changes in our discipline, and therefore we should be able to count on a new box of tools. In a metaphorical sense, I will call these tools a set of premises that should never be lacking in the future; we must be alert to the signs of change, the omens and the previous experiences of local communities. These pandemic times have prioritized the voices of “experts”, who impose hegemonic scientific systems as if they were the only option. Indigenous peoples are neither heard nor valued, even though they are some of the worst affected by this pandemic, being subject to large-scale ethnocide at this moment. Our challenge as ethnobiologists should be to build bridges and be agents of change, so that multiculturality and interculturality can be made visible and promoted.